Haemobilia of a 17 Years Girl Following Road Traffic Accident - Hoque, Md Rajibul; Alievna, Mostakim Maria; Rahman, Ayesha; Talukder, Md Tuhin; Saha, Tapan Kumar (Journal of Surgical Sciences, 2020)
Haemobilia is a rare cause of gastrointestinal bleeding, which develops as a result of communication between blood vessel and biliary tract. It should be considered in patients presenting with upper gastrointestinal bleeding with prior history of blunt trauma abdomen. We present a case of 17 years girl who sustained blunt trauma abdomen due to road traffic accident. She developed hematemesis & melena with bleeding from the wound after laparotomy for liver injury. Endoscopy of upper gastrointestinal tract revealed blood coming from ampulla of vater. CT angiography of abdomen showed pseudoaneurysm in a branch of right hepatic artery. Patient recovered completely after therapeutic embolization. Journal of Surgical Sciences (2019) Vol. 23 (1) : 40-42